The rural economic development of the magisterial district of Albert since 1865. - Van den Heever, Daniel Johannes Gertruida (Department of Environmental and Geographical Science, 2023)
Albert 1s situated 1n the North-East of the Cape Province,(see accompanying rough sketch map) bounded by the Orange River.1n the North and by the districts of Colesberg, steyneburg, Molteno, Wodehouse and Aliwal Borth in the Cape Province